PENGARUH KOMPETENSI, INDEPENDENSI, MOTIVASI, DAN AKUNTABILITAS TERHADAP KUALITAS AUDIT (Studi Empiris Pada Aparat Inspektorat Provinsi Jawa Tengah) - Nolanda Dwi Karnia; Haryanto Haryanto (Diponegoro Journal of Accounting, 2015)
This research was aimed to analyze the influence of competence, independence, motivation, and accountability to audit quality.The population in this study is Inspectorate officers of Central Java. Data retrieved through questionnaires. Total of questionnaires distributed as many as 60, but only 48 questionnaires can be processed. This study uses analysis of multiple linear regression.Results from this study indicate that the competence, independence, and accountability, and significant positive effect on audit quality. While the motivation variable has no significant effect on audit quality.